Engineering economic analysis of solar energy investments using spherical fuzzy sets - Onar, Sezi Cevik; Oztaysi, Bazar; Kahraman, Cengiz; Otay, Irem (World Scientific Publ Co Pte Ltd, 2020)
Solar energy is a reliable energy source that is important for the environmental sustainability. Solar energy investments become crucial for the countries like Turkey that does not have natural fossil based fuels but has a great potential of solar energy. In order to give better solar energy investment decisions, the uncertainties and ambiguities inherit in the investment decisions should be considered. Spherical fuzzy sets enable us to deal with uncertainty and ambiguity. The membership, non-membership and the hesitancies are considered in Spherical fuzzy sets, In this study a Spherical fuzzy set based net present worth analysis is proposed to deal with uncertain solar energy investments. The applicability of the proposed model is shown by an application. In this application, a solar power plant investment is evaluated by using the proposed model.
15th Symposium of Intelligent Systems and Knowledge Engineering (ISKE) held jointly with 14th International FLINS Conference (FLINS) -- AUG 18-21, 2020 -- Cologne, GERMANY
Keywords: Spherical Fuzzy Sets; Net Present Value; Solar Energy; İnvestment Analysis